Social dynamics and spatial design: A behavioral architecture study of adolescent gathering patterns - Khaerunisa, Silviana (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: City parks are important social spaces, especially for teenagers, but the design of public open spaces often does not take behavioral aspects into account. Previous studies have focused more on the physical function of open spaces than on user behavior. This paper analyze the influence of layout and design elements (paths, seating, trees, lighting) on the social interaction patterns of adolescents. Methods: Behaviorist case study (Yin), non-participatory observation, behavior mapping, and in-depth interviews. Findings: The study found that Indonesia Kaya Parks a functions as an inclusive third place for adolescents, where spatial elements like flexible seating, shaded vegetation, and warm lighting significantly enhance the frequency and quality of informal social interactions. It was found that zones with warm lighting, dense vegetation, and flexible seating became centers of social interaction. Conclusion: The spatial configuration and micro-design elements of Indonesia Kaya Parks effectively accommodate adolescents’ behavioral needs, confirming its role as a socially responsive urban park. Novelty/Originality of this article: This research uniquely combines quantitative data with spatial-perceptual mapping to reveal how adolescents navigate and emotionally respond to varying degrees of spatial enclosure in public parks—an approach rarely applied in behavioral architecture studies.